ANALISIS KRIMINOLOGI TERHADAP KEJAHATAN PERJUDIAN ONLINE DI WILAYAH HUKUM KEPOLISIAN DAERAH BALI - I Gusti Ngurah Agus Eka Yudha Pratama (Fakultas Hukum Universitas Dwijendra, 2021)
Abstrak Crime is all forms of actions and actions that are economically and psychologically harmful that violate the laws that apply in the Indonesian state as well as social and religious norms. The form of crime that has recently been rampant and very worrying is online gambling. Currently, online gambling crimes are still rife in the community due to the lack of maximum law enforcement against online gambling actors. Based on the background of the problem that the author has described above, it can be concluded that several problems were raised in this study, namely as follows: What are the factors that cause online gambling crimes in the Bali Regional Police jurisdiction? And what are the efforts made by the Police in tackling online gambling crimes within the jurisdiction of the Bali Regional Police? The research method used in this study is an empirical legal research method. Empirical legal research is the subject of the study, which is the law that is conceptualized as actual behavior as an unwritten social phenomenon that is experienced by everyone in social life relationships. Factors causing online gambling crimes in the Bali Regional Police jurisdiction where these factors are internal factors and external factors. Internal factors come from the perpetrators of these crimes which consist of low Human Resources (HR) and internet abuse factors. In addition to internal factors, there are also other factors where these factors are external factors where these factors come from outside the perpetrators of the crime where the external factors are economic factors, community factors not obeying the law and environmental factors. Efforts made by the Police in tackling online gambling crimes in the Bali Regional Police jurisdiction include Pre-Emtif Efforts by instilling moral values ​​to the younger generation as well as conducting counseling to the Polres to always be aware of online gambling crimes, preventive efforts in the form of conducting education, Closing good sites that smell like online gambling, and Carrying out monitoring and repressive efforts in the form of conducting investigations, conducting investigations, making arrests, conducting searches, conducting detentions, sealing places that have been proven to be hotbeds for online gambling activities , and Develop the information of the perpetrators who have been caught before.